Conducta obstétrica en paciente multípara de 24 años con embarazo de 38.5, trabajo de parto, hemorragia pos parto e histerectomía. - Olalla Correa, Jennifer Andrea (2022)
Postpartum hemorrhage is a frequent complication with a high rate of maternal morbidity and mortality. It is considered one of the main causes of maternal death in Ecuador, with uterine atony being the main cause (50% to 70% of cases). Its treatment consists of pharmacological measures to surgical procedures such as hysterectomy. The purpose of this clinical case was to analyze the obstetric behavior in a 24-year-old multiparous patient with a pregnancy of 38.5, labor, postpartum hemorrhage and hysterectomy, in addition to indicating the importance of a correct assessment to initiate the appropriate treatment. We present a 24-year-old patient admitted to the emergency room, due to moderate to high intensity contractile pain in the hypogastrium, she was assessed and the corresponding obstetric follow-up was carried out during delivery, a newborn was obtained by eutocic delivery, without complications, however During the immediate postpartum period, abundant bleeding is evident, without the presence of tears or lacerations, which is why uterine atony is presumed to be the cause. The red key is activated, and non-surgical measures are started to stop the bleeding. Despite this, good control of the bleeding is not achieved, which is why it is decided to perform a hysterectomy. It was concluded that a correct and timely diagnosis of postpartum bleeding will allow the corresponding treatment to be initiated, in order to avoid complications that may be fatal, and in this way, favorable maternal results will be obtained and the rate of maternal deaths from this cause will be reduced.